Jurnal Akuntansi & Investasi:Pengaruh Ownership Retention,Reputasi Auditor,Laba Perusahaan,n Underpricing trhdp Nilai Perusahaan dgn Kepemilikan Manajerial n Institusional Sebgai Variabel Pemoderasi - Barbara Gunawan, Mazda Halim (Akuntansi FE UMY, 2012)
This research aims to examine the effect of ownership retention (OR), auditors reputation, companys profit and underpricing on the value of the firm after an initial public offering and the moderating effect of managerial ownership and institutional ownership variables on the relationship between the proportion of retained ownership with value of the firm after the initial public offering.